Natural Justification in the Beauty of Nature —— From the Book of the Sick Plum Pavilion - Fang, Chulin (Transactions on Social Science, Education and Humanities Research, 2024)
The differences between Chinese civilization and Western culture have given rise to multiple interpretations of aesthetic concepts. In the academic field, studies on this topic are rich and in-depth. The source of this tendency lies in the continuation and evolution of the East and the West in natural justification, and the literary works of the two places, such as Gong Zizhen’s a Tale of the Sick Plum Pavilion, as well as Baudelaire’s Flowers of Evil, are deeply influenced by it. From literary criticism, philosophical scrutiny and aesthetic analyses, using The Tale of the Sick Plum Pavilion and Flowers of Evil as texts to address the inheritance or decline of natural beauty in the nineteenth century, it can help us to re-examine aesthetics and philosophy using the vision of aesthetic contemporaneity.